Kinetics of solutes and particles of different size in the digestive tract of cattle of 0.5–10 years of age, and relationships with methane production. Issue 3 (29th December 2017) - Grandl, F.; Schwarm, A.; Ortmann, S.; Furger, M.; Kreuzer, M.; Clauss, M.
Summary: The digestive physiology of cattle is characterised by comparatively long digesta mean retention times (MRTs), a particle sorting mechanism (difference in MRTs of large vs. small particles) and a distinct digesta washing (difference in MRTs between particles and fluids) in the reticulorumen (RR). How these processes mature during ontogeny, and how they link to other digestion characteristics and methane production, is largely unknown. We used a set of passage markers (Co‐EDTA for fluids and hay particles of 2, 5 and 8 mm length mordanted with Cr, La and Ce, respectively) to measure MRTs in 12 heifers (0.5–2.1 years; hay only) and two groups of 15 lactating cows (2.4–10.0 years; forage‐only vs. forage‐concentrate diet). The MRTs differed between markers (Co < Cr < La < Ce) and were longer in heifers than cows, consistent with the lower feed intake in heifers. MRTs were mostly similar between cow groups and increased with age. Digesta washing was not affected by group, age, feed intake and number of chews per unit of feed. The degree of digesta washing was not related to CH4 measures. Particle sorting was more prominent in cows than heifers but did not differ between cow groups or change with age in cows. This could be the consequence of the abrupt increase in intake from heifers to cows at a time when gut capacity is not yet fully developed; particle sorting might then clear smaller particles from the RR sooner allowing a higher intake. Surprisingly, CH4 yield per ingested feed did not correlate with MRTs, and CH4 yield per unit of digested fibre decreased with increasing MRTs and with increasing fibre digestibility. As this pattern occurred in heifers and both cow groups, it appeared independent of age, indicating a mechanism that has not been described in the literature so far and requires further investigation.